KUALITAS LAYANAN ELEKTRONIK, HARGA DAN PERSEPSI MANFAAT FITUR GO-PAY TERHADAP KEPUASAN PELANGGAN GOJEK DI KOTA PADANG - Fadhillah Aliyah; Wiry Utami; Irda Irda (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2021)
This study examines the relationship between the effect of electronic service quality, price and perceived benefits of go-pay features on customer satisfaction in Padang. Population in this study are all motorcycle customers who use the go-pay feature. With a sample size of 100 respondents selected using the Purposive Sampling technique. The results showed that electronic service quality has positive and significant effect on customer satisfaction, price has positive effect on customer satisfaction, while the perceived benefits does not significant on customer satisfaction.